Biodiversity conservation in agricultural landscapes: challenges and opportunities of coffee agroforests in the Western Ghats, India - García, C.A.; Bhagwat, S.A.; Ghazoul, J.; Nath, C.D.; Nanaya, K.M.; Kushalappa, Cheppudira G.; Raghuramulu, Y.; Nasi, Robert; Vaast, Philippe (2010)
The new approaches advocated by the conservation community to integrate conservation and livelihood development now explicitly address landscape mosaics composed of agricultural and forested land rather than only protected areas and largely intact forests. We refer specifically to a call by Harvey et al. (2008) to develop a new approach based on six strategies to integrate biodiversity conservation with sustainable livelihoods in Mesoamerican landscape mosaics. We examined the applicability of this proposal to the coffee agroforests of the Western Ghats, India. Of the six strategies, only one directly addresses livelihood conditions. Their approach has a clear emphasis on conservation and, as currently formulated risks repeating the failures of past integrated conservation and development projects. It fails to place the aspirations of farmers at the core of the agenda. Thus, although we acknowledge and share the broad vision and many of the ideas proposed by this approach, we urge more balanced priority setting by emphasizing people as much as biodiversity through a careful consideration of local livelihood needs and aspirations.